Depinning and vortex-glass-like transition in Nb with uncorrelated disorder - Oliveira, A. A M; Lisboa Filho, Paulo Noronha [UNESP]; Ortiz, W. A. (IOP Publishing, 2008)
Studies of the third harmonic of the AC-susceptibility were conducted to detect the boundaries of the linear regime of the magnetic response of granular Nb samples. These studies reveal the extent of the region, on the phase diagram, where the magnetic response is linear, which corresponds to the disordered phase of Vortex Matter. The present work addresses the correlation between a linear response and experimental parameters such as the frequency and the amplitude of the excitation field. The order-disorder border has been extracted from the onset temperature of the third harmonic measured at low-frequencies and low-excitation fields in the presence of dc magnetic fields. © 2008 IOP Publishing Ltd.